The actual, long-term cost of intentional injury care among a cohort of Maryland Medicaid recipients. Issue 3 (March 2022) - Dezman, Zachary D.W.; Thurman, Paul; Stockwell, Ian
Abstract : BACKGROUND: Intentional injury (both self-harm and interpersonal) is a major cause of morbidity and mortality, yet there are little data on the per-person cost of caring for these patients. Extant data focus on hospital charges related to the initial admission but does not include actual dollars spent or follow-up outpatient care. The Affordable Care Act has made Medicaid the primary payor of intentional injury care (39%) in the United States and the ideal source of cost data for these patients. We sought to determine the total and per-person long-term cost (initial event and following 24 months) of intentional injury among Maryland Medicaid recipients. METHODS: Retrospective cohort study of Maryland Medicaid claims was performed. Recipients who submitted claims after receiving an intentional injury, as defined by the International Classification of Diseases, Tenth Revision, between October 2015 and October 2017, were included in this study. Subjects were followed for 24 months (last participant enrolled October 2017 and followed to October 2019). Our primary outcome was the dollars paid by Medicaid. We examined subgroups of patients who harmed themselves and those who received repeated intentional injury. RESULTS: Maryland Medicaid paid 11, 757, 083 for the care of 12, 172 recipients of intentional injuries between 2015 and 2019. The per-person, 2-year health care cost of an intentional injury was a median of 183 (SD, 5, 284). These costs were highly skewed: min, 2.56; Q 1 = 117.60, median, 182.80; Q 3 = 480.82; and max, 332, 394.20. The top 5% (≥95% percentile) required 3, 000 (SD, 6, 973) during the initial event and 8, 403 (SD, 22, 024) per served month thereafter, or 55% of the overall costs in this study. CONCLUSION: The long-term, per-person cost of intentional injury can be high. Private insurers were not included and may experience different costs in other states. LEVEL OF EVIDENCE: Economic and Value Based Evaluations; level III.